Tumor hypoxia-activated combinatorial nanomedicine triggers systemic antitumor immunity to effectively eradicate advanced breast cancer. (June 2021) - Liu, Jing; Ai, Xixi; Cabral, Horacio; Liu, Jinlu; Huang, Yuan; Mi, Peng
Abstract: Hypoxia is a major obstacle towards successful cancer treatment, due to the hypoxia-mediated resistance to radiotherapy and chemotherapy, as well as immunosuppression. Therefore, engineering hypoxia-sensitive cytotoxic and immunogenic nanomedicines would promote the therapeutic efficacy. In this study, we developed novel tumor-targeted polymeric micelles sensing hypoxia in tumors to activate strong cytotoxicity and immunogenic responses for effectively eradicating advanced breast cancer. The hypoxia-activatable polymeric micelles could efficiently deliver anticancer drugs and photosensitizers into cancer cells, to trigger synergistic cytotoxicity and immunogenic cell death through chemotherapy and photodynamic therapy (PDT)/photothermal therapy (PTT). The long-circulating micelles efficiently delivered drugs to triple negative 4T1 breast tumors for accurate tumor diagnosis by photoacoustic imaging (PA), and effectively eliminating primary tumors without recurrence, including hypoxic 4T1 tumors. In addition, the micelle-based eradication of primary tumors could elicit robust systemic immune responses to inhibit tumor recurrence and significantly suppress distant 4T1 tumors and lung metastasis by combining with CpG and aCTLA4. These results indicate the high performance of our innovative multifunctional micelles for synergistic therapy against tumor malignancy, bringing opportunity for effectively dealing with disseminated and metastatic tumors.